Sugar-derived compounds for gelation of various solvents and forming supramolecular dual-network materials for 3D printing applications - Dizon, Glenieliz (2022)
Low molecular weight gelators (LMWGs) are a class of organic compounds with molecular weights of less than 2000 Da that show gelation behaviour in a solvent. In recent years, LMWGs have been the subject of intensive research from material, synthetic, supramolecular, and biological chemists. They are an essential class of functional materials, finding applications in various industries such as cosmetics, food processing, healthcare and many more. During the development of soft material systems inspired by green chemistry, this research shows that naturally occurring starting materials can prepare benzylidene sorbitol and xylitol derivatives. These compounds gelate a range of organic solvents, aqueous mono- and divalent salt solutions, photocurable monomers, DMSO/water solutions, and ethanol-water solutions, with the equimolar mixture of two of the gelators gelling all compositions from 100% ethanol to 100% water (something neither of the individual components does). We explored the influence of modifications to the acetal substituents on the formation of the compounds and the impact of steric bulk on the self-assembly properties of the gelators. The effect of solvent on the self–assembly, morphology, and rheology of the 1,3:2,4-di(4-isopropylbenzylidene)-D-sorbitol (DBS-iPr), 2,4(4-isopropylbenzylidene)-D-sorbitol (MBS-iPr) and the equimolar multicomponent (DBS-MBS-iPr) gels have been investigated using scanning electron microscopy (SEM). By virtue of lamellar segregation of hydrophilic and hydrophobic regions of the molecules, DBS-iPr gelates polar solvents to form smooth flat fibres. In non-polar solvents such as cyclohexane, aided by strong hydrogen bonding interactions, it results in helical fibres where the chirality is determined by the stereochemistry of the sugar. Oscillatory rheology revealed that MBS-iPr gels have appreciable higher strength and elasticity than DBS-iPr gels, regardless of the solvent medium employed. Powder X-ray diffraction was used to probe the arrangement of the gelators in the xerogels they form, and two single-crystal X-ray structures of related MBS derivatives give the first precise structural information concerning layering and hydrogen bonding in the monobe highernzylidene sorbitol compounds. This kind of layering could explain the apparent self-sorting behaviour of the DBS-MBS-iPr multicomponent gels.